658 Toxicities of single agent and combination immune checkpoint inhibitors in patients with pre-existing autoimmune diseases. (9th November 2020) - Sandigursky, Sabina; Houssein, Safa; Pundole, Xerxes; Efuni, Elizaveta; Cytryn, Samuel; Buni, Maryam; Pavlick, Anna; Krogsgaard, Michelle; Saberian, Chantal; Altan, Mehmet; Suarez-Almazor, Maria; Weber, Jeffrey; et al.
Abstract : Background: Autoimmunity is associated with increased risk of malignancy. However, patients with pre-existing autoimmune diseases (AIDs) were excluded from immune checkpoint inhibitor (ICI) trials as these agents can cause immune-related adverse events (irAEs). Data are limited on the safety and efficacy of combination immunotherapy in this at-risk population. Methods: We conducted a multi-center retrospective study to evaluate the safety and efficacy of ICI therapy in patients with pre-existing AID treated at NYU and at MD Anderson Cancer Center. Primary endpoints were occurrence of irAEs and AID flares. Secondary endpoints were time to treatment failure (TTF) and overall survival (OS). Results: Of 121 patients identified from our institutional databases, 53% received single-agent anti-PD-1 therapy, and 47% received ICI combination. Over half of malignancies were lung cancer (34%) and melanoma (20%). Preexisting AIDs included: rheumatologic (58%), gastrointestinal (12%), endocrine (16%) and neurologic (4%). Overall, 94% had asymptomatic AID, and 21% were receiving systemic immunomodulatory drugs at ICI initiation. Median duration of follow up after ICI initiation was 9 (0.4–41.9) months in patients receiving ICI combination and 8 (0.2–47.3) months in patients receiving anti-PD-1 monotherapy. Combination therapy was associated with higher rates of irAEs compared with anti-PD-1 monotherapy (56% versus 28%). Grade 3/4 irAEs were equivalent in both groups: combination (38%) and anti-PD-1 group (39%). Treatment related deaths were not observed in any group. AID flares occurred in 36% of the anti-PD-1 group versus 29% of combination group. Adverse events (irAEs and/or flares) required systemic immunomodulatory therapies more frequently in the combination group (84%) versus the anti-PD-1 group (59%), and permanent ICI discontinuation was reported in 19% of patients in the combination group versus 11% in the anti-PD-1 group. Tumor progression was observed in 49% of patients on combination ICI and TTF was 14.5 months (95% CI 0.000–31.5), while progression was observed in 64% of patients on anti-PD-1 monotherapy and TTF was 6.4 months (95% CI 4.01–8.9) (p=0.019). Median OS in the combination therapy group was not reached whereas it was 27.3 months in the anti-PD-1 monotherapy group. Conclusions: Our novel findings suggest that high rates of adverse events were observed in patients with pre-existing AIDs treated with ICI combination therapy. However, they were manageable and rarely required permanent ICI discontinuation. Taken together, these data show that ICIs should be offered, albeit with caution in patients with AIDs, to achieve durable cancer remission. Prospective clinical data are needed to guide these complex decisions. Ethics Approval: The study was approved by NYU Langone's Ethics Board, approval number i18-01657 and MD Anderson's Ethics Board, approval number PA19-0089